Physiological and genetic analysis of root responsiveness to auxin-producing plant growth-promoting bacteria in common bean (Phaseolus vulgaris L.) - Remans, R; Beebe, Stephen E.; Blair, Matthew W.; Manrique, G; Tovar Luque, E.; Rao, Idupulapati M.; Croonenborghs, A; Torres Gutierrez, R; El-Howeity, M; Michiels, J; Vanderleyden, J (Springer, 2008)
Plant root development can be largely affected through the association of roots with plant growth-promoting rhizobacteria (PGPR). However, little is known about the identity of plant genes enabling such PGPR-plant root associations. Differences in the responsiveness to PGPR among cultivars suggest genetic variation for this trait within germplasm. In this study, two genotypes of common bean (Phaseolus vulgaris L.), BAT477 and DOR364, were identified showing contrasting responsiveness in root development to inoculation with the PGPR Azospirillum brasilense Sp245. Inoculation with an A. brasilense Sp245 mutant strain strongly reduced in auxin biosynthesis or addition of increasing concentrations of exogenous auxin to the plant growth medium, indicated that the differential response to A. brasilense Sp245 among the bean genotypes is related to a differential response to the bacterial produced auxin. To further assess the role of the plant host in root responsiveness, a population of Recombinant Inbred Lines (RILs) of the DOR364×BAT477 cross was used to evaluate the efficacy of exogenous auxin on root development. We detected significant phenotypic variation among the RILs for basal root formation during germination upon addition of auxin to the growth medium. Genetic analysis revealed two quantitative trait loci (QTLs) associated with basal root responsiveness to auxin of which one explained 36% of the phenotypic variation among the RILs. This latter QTL mapped to the same location as a QTL for root tip formation at low P, suggesting that the host effect on root responsiveness to IAA interacts with specific root development. Also, significant correlations between basal root responsiveness to auxin and growth, root tips and root dry weight at low P were identified. To our knowledge, this is the first report on QTL detection for root responsiveness to auxin.